Perancangan Aplikasi Informasi Lowongan Pekerjaan Berbasis Android - Goldy Widiyanto; Henri Septanto (UNIVERSITAS KALBIS, 2022)
The purpose of this research is to produce an android based job search application. This job finder application was made for job seekers and also those people who are looking for human resources. Job vacancies that created by human resource seekers will searching for human resources whose have expertise is in accordance with what's human resource seeker looking for and then provide notifications with connected Firebase Cloud Messaging (FCM) to do push notifications to job seekers so that they will know if there is a suitable job with their expertise. The development method used in this research is Rational Unified Process (RUP) with Unified Modeling Language (UML) for system modelling. This application was built with Android Studio software using the Java programming language, XML, Laravel framework also uses the PHP programming language and uses a MySQL database. The final result of this research is an android-based job opening application.